Regulation of intestinal health and disease by innate lymphoid cells. (12th May 2014) - Sonnenberg, Gregory F.
Abstract : Intestinal innate lymphoid cells Abstract: Innate lymphoid cells (ILCs) are a recently appreciated immune cell population that is constitutively found in the healthy mammalian gastrointestinal (GI) tract and associated lymphoid tissues. Translational studies have revealed that alterations in ILC populations are associated with GI disease in patients, such as inflammatory bowel disease, HIV infection and colon cancer, suggesting a potential role for ILCs in either maintaining intestinal health or promoting intestinal disease. Mouse models identified that ILCs have context-dependent protective and pathologic functions either during the steady state, or following infection, inflammation or tissue damage. This review will discuss the associations of altered intestinal ILCs with human GI diseases, and the functional consequences of targeting ILCs in mouse models. Collectively, our current understanding of ILCs suggests that the development of novel therapeutic strategies to modulate ILC responses will be of significant clinical value to prevent or treat human GI diseases.